Elucidation of naphthalene diimide metallomacrocycles and catenanes by solvent dependent excimer and exciplex emission. Issue 5 (19th December 2018) - Boer, Stephanie A.; Cox, Rosalind P.; Beards, Michael J.; Wang, Huixin; Donald, William A.; Bell, Toby D. M.; Turner, David R.
Abstract : The formation of metallocatenanes, and their disruption by aromatic solvents, is followed by excimer and exciplex emission. Abstract : Metallomacrocycles and [2]-catenanes based on a leucine substituted naphthalene diimide ligand have been confirmed in solution through detection of excimer and exciplex emission. Comparison with the behaviour of the free ligand provides insight into the solution speciation of the metallosupramolecular complexes and their solvent dependent nature.